The influence of the pollination compatibility type on the pistil S-RNase expression in European pear (Pyrus communis) - Claessen, Hanne; Palmers, Han; Keulemans, Wannes; Van de Poel, Bram; De Storme, Nico (Frontiers in Genetics, 2024)
The S-RNase gene plays an essential role in the gametophytic self-incompatibility (GSI) system of Pyrus. It codes for the stylar-expressed S-RNase protein which inhibits the growth of incompatible pollen tubes through cytotoxicity and the induction of programmed cell death in the pollen tube. While research on the Pyrus GSI system has primarily focused on the S-RNase gene, there is still a lack of insight into its spatiotemporal expression profile and the factors that regulate it. Previous studies have suggested that S-RNase expression in the style is influenced by pollination and is dependent on the compatibility type. We here continue on this basic hypothesis by analyzing the spatiotemporal expression of the S-RNase alleles in Pyrus communis "Conference" styles in response to different types of pollination; namely upon full-and semi-compatible pollination and upon incompatible selfing. The results revealed that temporal dynamics of S-RNase expression are influenced by the pollen's compatibility type, indicating the presence of a signaling mechanism between pollen and style to control S-RNase production during pollen tube growth. In our experiment, S-RNase expression continuously decreased after cross-pollination and in the unpollinated control. However, after a fully incompatible pollination, S-RNase expression remained constant. Finally, semi-compatible pollination showed a initially constant S-RNase expression for both alleles followed by a strong decrease in expression. Based on these results and previous findings, we propose a regulatory mechanism to explain the effect of pollination and the associated compatibility type on S-RNase expression in the style. This proposed mechanism could be used as a starting point for future research.